Evaluation of hypertension treatment in acute ischemic stroke - Lara Haidar; Hiba AlHarfany; Sarah G. Cherri; Diana Malaeb; Nada Dia; Pascale Salameh; Hassan Hosseini (Elsevier, 2021)
Background: Treating hypertension (HTN) in acute ischemic stroke (AIS) is controversial, since both extremely high and low blood pressures (BP) are associated with poor outcomes. Objective: This study was designed to describe and assess the frequency and the factors affecting BP overtreatment in AIS. Methods and material: This was a retrospective observational study conducted at Lebanese hospitals. BP readings at baseline and after treatment with antihypertensive drugs were recorded. Overtreatment was defined as baseline BP below 220/120 mmHg and an antihypertensive drug was prescribed. Results: A total of 141 patients were enrolled with a mean age of 76.89 years and 43.3% were males. Overtreatment rate was 62.6%, and was significantly more common in patients with a previous history of HTN and hyperlipidemia. In addition, overtreatment was significantly more common in patients treated with antihypertensive drugs, had high modified Rankin Scale score (>2) at baseline, and had high systolic BP at baseline (p < 0.05). Results of multivariate analysis revealed that the highest risk of overtreatment was significantly shown in patients who had HTN (OR = 4.589, p = 0.017), and who had high systolic BP at baseline (OR = 1.061, p = 0.001). Conclusion: BP management in AIS was generally not consistent with the guidelines. This supports the need for further research to investigate the effects of BP overtreatment on patient outcomes.